Adquisición de métricas para el servicio de Vídeo 360/VR - Peñaherrera-Pulla, Oswaldo Sebastián; Baena-González, José Carlos; Fortes-Rodríguez, Sergio; Baena-Martínez, Eduardo; Barco-Moreno, Raquel (My University, 2021)
Virtual Reality (VR) arises as one of the current cutting-edge technologies. Its applications address educational and entertainment uses. This work presents a framework to assess video 360 service performance over VR headsets through Key Quality Indicators (KQIs). This service differs from traditional video streaming approaches due to its immersive experience, which allows the user to enjoy omnidirectional multimedia. However, the service experience must be guaranteed in order to avoid side effects such as cybersickness or disorientation. The testbed is conformed by a Unity video player, which reproduce multimedia sources (DASH and HLS) from a video server located in the cloud while KQI measuring tasks are performed. Finally, a performance comparison between technologies is provided. Results from the KQI measurement highlight the potential of the new generation of mobile networks in the provision of service with high-quality levels of experience.
Keywords: Realidad virtual - Valoración; Telecomunicaciones, Sistemas de - Valoración; VR; Vídeo 360; Redes móviles; Calidad de experiencia